Principles of Biomechanics - Huston, R. (CRC Press, 2008)
Research and study in biomechanics has grown dramatically in recent years, to the extent that students, researchers, and practitioners in biomechanics now outnumber those working in the underlying discipline of mechanics itself. Filling a void in the current literature on this specialized niche, Principles of Biomechanics provides readers with a solid grasp of the fundamentals and the enabling procedures of this rapidly expanding field, placing a sharp focus on dynamic phenomena in the area of whole-body biomechanics.